Laboratory measurements of heterogeneous CO2 ice nucleation on nanoparticles under conditions relevant to the Martian mesosphere. Issue 5 (5th May 2016) - Nachbar, Mario; Duft, Denis; Mangan, Thomas Peter; Martin, Juan Carlos Gomez; Plane, John M. C.; Leisner, Thomas
Abstract: Clouds of CO2 ice particles have been observed in the Martian mesosphere. These clouds are believed to be formed through heterogeneous nucleation of CO2 on nanometer‐sized meteoric smoke particles (MSPs) or upward propagated Martian dust particles (MDPs). Large uncertainties still exist in parameterizing the microphysical formation process of these clouds as key physicochemical parameters are not well known. We present measurements on the nucleation and growth of CO2 ice on sub‐4 nm radius iron oxide and silica particles representing MSPs at conditions close to the mesosphere of Mars. For both particle materials we determine the desorption energy of CO2 to be Δ F des  = (18.5 ± 0.2) kJ mol −1 corresponding to Δ F des  = (0.192 ± 0.002) eV and obtain m  = 0.78 ± 0.02 for the contact parameter that governs heterogeneous nucleation by analyzing the measurements using classical heterogeneous nucleation theory. We did not find any temperature dependence for the contact parameter in the temperature range examined (64 K to 73 K). By applying these values for MSPs in the Martian mesosphere, we derive characteristic temperatures for the onset of CO2 ice nucleation, which are 8–18 K below the CO2 frost point temperature, depending on particle size. This is in line with the occurrence of highly supersaturated conditions extending to 20 K below frost point temperature without the observation of clouds. Moreover, the sticking coefficient of CO2 on solid CO2 was determined to be near unity. We further argue that the same parameters can be applied to CO2 nucleation on upward propagated MDPs. Key Points: Measurements on heterogeneous nucleation of CO2 on meteoric smoke particle analogues Evaluation of contact parameter, desorption energy, and sticking coefficient Extreme cold conditions are needed to affect CO2 nucleation in the Martian mesosphere